2014
DOI: 10.1093/jjco/hyu182
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sublingual fentanyl orally disintegrating tablet at doses determined from oral morphine rescue doses in the treatment of breakthrough cancer pain

Abstract: Patients treated with strong opioid analgesics at fixed intervals for chronic cancer pain and with oral morphine at doses up to 20 mg as rescue medication were investigated. The doses of sublingual fentanyl to treat breakthrough pain were determined from rescue morphine doses by use of conversion ratios. In these patients, administration of sublingual fentanyl at doses determined by a conversion ratio of 1/50 was effective and safe. Further studies are needed to validate the use of this conversion method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…The total number of participants in different studies was 1,004 patients. [15][16][17][18][19][20][21][22][23][24][25][26] ( Figure 1) 1 of the studies was conducted in the USA, 1 in the UK, 1 in Japan, 1 in the Netherlands, 1 in India, 1 in Europe and Indian, 1 in Spain and 5 were conducted in Italy. The study period varied between 1997 to 2017.…”
Section: Results Study Selection and Characteristicsmentioning
confidence: 99%
“…The total number of participants in different studies was 1,004 patients. [15][16][17][18][19][20][21][22][23][24][25][26] ( Figure 1) 1 of the studies was conducted in the USA, 1 in the UK, 1 in Japan, 1 in the Netherlands, 1 in India, 1 in Europe and Indian, 1 in Spain and 5 were conducted in Italy. The study period varied between 1997 to 2017.…”
Section: Results Study Selection and Characteristicsmentioning
confidence: 99%
“…However, there has been a study suggesting doses of a transmucosal immediate-release buccal fentanyl formulation proportional to a patient's ATC opioid regimen was more efficacious than oral morphine during the first 30 min posttreatment [32]. Another approach calculated the dose of a transmucosal immediate-release sublingual fentanyl formulation for BTCP from a precalculated morphine dose for BTCP and found that a conversion ratio of 1/50 provided efficacious analgesia [33]. In the current study, initiating treatment with a low dose of a fentanyl sublingual spray and titrating upward to identify an effective dose, was found to be an efficacious strategy for patients receiving ATC transdermal fentanyl patch.…”
Section: Discussionmentioning
confidence: 99%
“… Shimoyama 2015 173,185 ; Farrar 1998 174 ; Portenoy 2006 and 2010 175,180 ; Slatkin 2007 176 ; Kress 2009 177 ; Rauck 2009, 2010, and 2012 178,181,182 ; Lennernäs 2010 179 ; Kosugi 2014 183 ; Novotna 2014 184 ; and Thronæs 2015 186 …”
Section: Methodsunclassified
“…Most randomized, placebo-controlled trials in the cancer pain field have evaluated fentanyl for breakthrough pain (acute episodes of pain superimposed on chronic/background cancer pain). A 2022 guideline identified 14 placebo-controlled trials (n = 1347) [173][174][175][176][177][178][179][180][181][182][183][184][185][186] of fentanyl administered via the sublingual (n = 5), intranasal (n = 3), buccal (n = 4), or oral transmucosal (spray) route (n = 2; Table 2; see Table S12).…”
Section: Placebo-controlled Trials For Breakthrough Cancer Painmentioning
confidence: 99%
See 1 more Smart Citation